An unusual cause of delayed postpartum haemorrhage following caesarean section. Issue 8 (22nd July 2009) - Samad, S; Jonetzko, P; Hawkins, A P; Booth, J; Thorpe-Beeston, G; Marwood, R
Abstract : Although less common in the UK, postpartum haemorrhage (PPH)—defined as blood loss of 500 ml or more within the first 24 h of delivery— remains a significant cause of maternal death worldwide. Haemorrhage between 24 h and 6 weeks post partum is termed "delayed PPH". Common causes include retention of gestational products or endometritis. Bleeding can be sudden and profound, resulting in rapid cardiovascular collapse. A case of massive PPH 7 weeks after a caesarean section caused by a pseudoaneurysm of the uterine artery is reported. This case highlights diagnostic and therapeutic issues concerning this rare but potentially life-threatening condition and presents clinical features distinguishing it from other causes of PPH. Delay in diagnosis can result in repeated and catastrophic bleeding.